ASPECTS OF NEPHROTOXICITY OF THE MOST USED NONSTEROIDAL ANTIINFLAMMATORY DRUGS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Spasovski, Dejan; Sandevska, Emilija; Genadieva stavrikj, Sonja; Sotirova, Tatjana; Krstevska Balkanov, Svetlana; Shubeska Stratrova, Slavica; Brezovska Kavrakova, Julijana (Македонско лекарско друштво = Macedonian medical association, 2021)
Introduction. Microalbuminuria is used as a marker for glomerular damage and urinary excretion of N-acetyl-D-glucosaminidase (NAG) as an indicator of proximal tubular damage. Aim. The aim of the study was to quantify the toxicity of these drugs by measuring the enzyme excretion that correlates with the degree of damage of the tubular epithelium. It was also our aim to determine the effects of the initial therapy with Etoricoxib and Diclofenac on glomerular and tubular integrity in patients suffering from rheumatoid arthritis (RA). Methods. By using the colorimetric method for determination of NAG, as well as the immunoturbidimetric method for detection of microalbuminuria, tests were performed in 70 participants (35 RA patients treated only with Etoricoxib, 35 RA patients with Diclofenac) in four-time intervals within the course of eight weeks. Results. There was a moderate correlation between NAG and microalbuminuria (r=0.21) in the group of patients treated with Etoricoxib, while there was a statistically significant correlation (r=0.28) in the group treated with Diclofenac. NAG enzymuria, in volume, by the number of participants in whom it was registerred and the time of its occurrence was much faster during the use of Diclofenac compared to Etoricoxib. Conclusion. Diclofenac is a potent NAG-inductor and gives a larger tubular enzymuria in comparison with Etoricoxib.
Keywords: N-acetyl-B-D-glucosaminidase; microalbuminuria; rheumatoid arthritis; Etoricoxib; Diclofenac